(untitled) (Indian Journal of Animal Production and Management, 2016)
The data on milk production performance of 342 HF X Gir halfbreds were collected from records maintained at Research Cum Development Project on Cattle, Mahatma Phule Krishi Vidyapeeth, Rahuri (Maharashtra) for a period from year 1974 to 2013. Overall mean of 43 individual weekly test day milk yield varied from 3.16±0.14 kg (WTDY43) to 13.52±0.14 kg (WTDY5). The overall mean lactation milk yield was 3457.33 ± 41.79 kg. Effect of period of calving on all 43 weekly test day milk yield was significant (Ps<0.01) except WTDY4. The influence of season and period of calving and age at first calving on lactation milk yield were significant (P<0.01). Phenotypic correlations among all test day milk yield ranged from 0.086 (WTDY1 with WTDY24) to 0.49 (WTDY32 with WTDY33). In HF X Gir halfbred heritability of lactation milk yield was 0.91 ± 0.15. The h2 of weekly test day milk yield ranged from 0.10 ± 0.48 (WTDY27) to 0.94 ± 0.44 (WTDY2).